Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species - Nielsen, Jørgen G. (Zootaxa, 2017)
The genus Nybelinella belongs to the aphyonid clade within the Bythitidae. This mainly abyssal genus is known from 30 specimens. The present revision is based on 24 specimens, of which a scientific examination of four specimens has been published earlier. As a consequence, the generic diagnosis from Nielsen et al. (1999) is here modified. Of the 24 specimens 22 are referred to N. erikssoni (Nybelin, 1957), one to N. brevidorsalis Shcherbachev, 1976 and one to a new species, N. brevianalis n. sp., herein described.